(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of this study was to see the association of lichen planus (n=80) with glucose metabolism disturbance. Classic variety of lichen planus was the most common (76.3%), followed by ashy dermatosis, hypertrophic, oral, actinic and nail lichen planus. The blood glucose level 2 hours after glucose drink was abnormal in 20 cases. HbA1c was abnormal in 7 cases. The mean homeostasis model of assessment formulation- insulin resistance index (HOMA-IR) was 2.1 ± 1.6 and it was higher (>4.8) in 12.5% patients. Diabetes mellitus was found in 30 patients. Impaired glucose tolerance was found in 15 cases and high HOMA-IR was found in 10 cases. Total number of cases of abnormal glucose metabolism was found in 55 (68.8%) cases of lichen planus. In conclusion, patients with lichen planus have higher risk of abnormal glucose metabolism specially diabetes mellitus.